Epithelial talin-1 protects mice from citrobacter rodentium-induced colitis by restricting bacterial crypt intrusion and enhancing t cell immunity. (31st December 2023) - Latour, Yvonne L.; Allaman, Margaret M.; Barry, Daniel P.; Smith, Thaddeus M.; Williams, Kamery J.; McNamara, Kara M.; Jacobse, Justin; Goettel, Jeremy A.; Delgado, Alberto G.; Piazuelo, M. Blanca; Zhao, Shilin; Gobert, Alain P.; et al.
ABSTRACT: Pathogenic enteric Escherichia coli present a significant burden to global health. Food-borne enteropathogenic E. coli (EPEC) and Shiga toxin-producing E. coli (STEC) utilize attaching and effacing (A/E) lesions and actin-dense pedestal formation to colonize the gastrointestinal tract. Talin-1 is a large structural protein that links the actin cytoskeleton to the extracellular matrix though direct influence on integrins. Here we show that mice lacking talin-1 in intestinal epithelial cells ( Tln1 Δepi ) have heightened susceptibility to colonic disease caused by the A/E murine pathogen Citrobacter rodentium . Tln1 Δepi mice exhibit decreased survival, and increased colonization, colon weight, and histologic colitis compared to littermate Tln1 fl/fl controls. These findings were associated with decreased actin polymerization and increased infiltration of innate myeloperoxidase-expressing immune cells, confirmed as neutrophils by flow cytometry, but more bacterial dissemination deep into colonic crypts. Further evaluation of the immune population recruited to the mucosa in response to C. rodentium revealed that loss of Tln1 in colonic epithelial cells (CECs) results in impaired recruitment and activation of T cells. C. rodentium infection-induced colonic mucosal hyperplasia was exacerbated in Tln1 Δepi mice compared to littermate controls. We demonstrate that this is associated with decreased CEC apoptosis and crowding of proliferating cells in the base of the glands. Taken together, talin-1 expression by CECs is important in the regulation of both epithelial renewal and the inflammatory T cell response in the setting of colitis caused by C. rodentium, suggesting that this protein functions in CECs to limit, rather than contribute to the pathogenesis of this enteric infection.